University Students’ Perceptions of Implementation of English Online Learning System - Djuria Suprato; Christiana Sidupa (Proceeding International Conference on Information Technology and Business, 2019)
This study was undertaken to find out whether the implementation of the English online learning system would give positive impacts for the students at BINUS University. The study was done by spreading a survey questionnaire with Google Form and through two forms of social media, such as Line and WhatsApp, had yielded responses from 38 students. The respondents supported this idea of implementing online learning for English subjects and had their personal reasons. Overallperceptions of online learning were positive. The majority of students in the online learning indicated that they would prefer if the approach was offered. Therefore, this research found that online learning for English subjects as applicable.Keywords: online learning, social media, English Subject, approach.